RANCANG BANGUN ALAT PEMOTONG KELAPA MUDA TIPE MANUAL Test of Effect of Number of oil expel holes channel of Peanut oil Pressing Semi Mechanical Equipment (Arachis hypogea L.) - M.Rezeki Murad Maldini Daulay; Saipul Bahri Daulay; Taufik Rizaldi (Universitas Sumatera Utara, 2018)
ABSTRACT As well as many countries in Pacific Ocean, Indonesia is a world main coconut producer. The cutting of coconut until this time is mainly using traditional equipment that still has many weaknesses. The application of mechanical technology in the form of efficient machine and equipment among farmers is really necessary to be developed so that the quantity and the quality of product can be improved. The aims of this research were to design, to build and to test the manual type of coconut cutter by using coconut as the material. The results showed that the effective capacity of this equipment was 75,91 pieces/hour, the average diameter of coconut that used in this research was 17,75 cm. Economic analysis showed that break even point was 783,037 pieces/year on the fifth year, net present value was Rp 94.831.471/year with 4,75% of interest rates and Rp 91.556.947/year with 6% of interest rates, and internal rate of return was 42,393%. Key word: manual type of coconut cutter, coconut, manual equipment ABSTRAK Seperti halnya negara-negara di Samudera Pasifik, Indonesia merupakan penghasil kelapa utama dunia. Pemotongan kelapa muda hingga pada saat sekarang ini masih banyak yang menggunakan peralatan tradisional yang masih memiliki banyak kelemahan. Penerapan teknologi mekanis dalam bentuk mesin dan peralatan tepat guna di kalangan petani sangat perlu untuk dikembangkan agar jumlah dan mutu produk dapat ditingkatkan. Penelitian ini bertujuan untuk mendesain, membuat dan menguji alat pemotong kelapa muda tipe manual dengan menggunakan kelapa muda sebagai bahan bakunya. Hasil penelitian menunjukkan bahwa kapasitas efektif alat sebesar 75,91 buah/jam, rata-rata diameter kelapa yang digunakan dalam penelitian berdiameter 17,75 cm. Analisis ekonomi menunjukkan bahwa break even point sebesar 783,037 buah/tahun pada tahun kelima, net present value sebesar Rp 94.831.471/tahun dengan suku bunga 4,75% dan Rp 91.556.947/tahun dengan suku bunga coba-coba 6%, serta internal rate of return sebesar 42,393%. Kata kunci: alat pemotong kelapa muda tipe manual, kelapa, alat manual